CAN CLEAR ALIGNERS THERAPY ACHIEVE MAXILLARY EXPANSION IN PATIENTS WITH TRANSVERSE MALOCCLUSIONS? A SYSTEMATIC REVIEW - Ibraheem Bamaga (Romanian Journal of Oral Rehabilitation)
Background: Clear aligners have become a pivotal advancement in orthodontic treatment, offering a viable alternative to traditional metal braces. Despite the reported benefits of clear aligners such as being more hygienic and aesthetic, some orthodontists remain sceptical about the effectiveness of aligners in achieving treatment goals. This uncertainty may arise due to traditional preferences or the perceived limitations in their ability to execute complex tooth movements. Aim of the study: This systematic review investigates the effectiveness of clear aligners in achieving dentoalveolar expansion of the maxillary arch. Materials and methods: An electronic search was conducted on PubMed, Web of Science, Google Scholar, and Scopus from January 2020 to July 2024 to identify relevant articles. Methodological shortcomings were highlighted, and an evaluation of the quality of the included studies was completed using the Risk of Bias in Non-randomised Studies of Interventions (ROBINS-I) tool. Results: Out of 453 studies identified, seven studies met the inclusion criteria and were included in this review. Four studies were on adult subjects with full permanent dentition and three were on subjects with mixed dentition. The risk of bias was generally minimal according to the ROBINS-I tool in all the studies reviewed. The efficacy of expansion with clear aligners was more prominent in the canine and premolar area, with the expansion mainly achieved with tipping movements rather than bodily translation movement. The planning software overpredicted the dental movements compared to what was achieved. Conclusions: Clear aligners primarily achieve expansion via dental tipping. Overcorrection and buccal root torque should be planned to ensure more bodily movements and expansion goals are met after treatment. Employing clear aligners in younger patients is particularly advantageous for upper arch development and correction of transverse malocclusions, especially in the canine segment.